Eksistensi OJK Sebagai Lembaga Surveuilance: Pembaharuan Hukum Perbankan - Ulima, Ajeng; Isnugraheny, Rizqika Farah; Megawati, Zahra Ekasiwi; Fitrada, Azzahra Hifz Aldin; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The establishment of the Financial Services Authority (OJK) in Indonesia marks an important step in the effort to strengthen banking law and financial sector supervision. This paper examines the role of the OJK as a supervisory agency in the context of Indonesian banking law, with an emphasis on its contribution to regulatory reform and consumer protection. This study uses a normative juridical approach, supported by a comprehensive literature review, to analyze the functioning of the OJK based on Law Number 21 of 2011 and its impact on banking governance. One of the OJK’s main responsibilities is overseeing compliance with sound banking practices and ensuring compliance with regulatory frameworks among financial institutions. The organization is also proactive in adapting regulations to new financial technologies, so it can address challenges arising from the rapid development of the fintech industry. Despite achieving progress, OJK still faces challenges in effective enforcement, resource allocation, and interagency collaboration. The paper concludes that although the OJK has made significant strides in improving the stability and integrity of the Indonesian banking system, additional measures are needed to strengthen its monitoring capabilities and address emerging risks. Recommendations include strengthening human resources, utilization of technology for greater efficiency, and increased public participation to ensure financial literacy. By strengthening its role as a regulator, the OJK can effectively navigate Indonesia’s complex and dynamic financial services landscape, ultimately protecting consumers’ interests and driving economic growth.